A Semi-Analytical Model for Pressure Transient Analysis of Multiple Fractured Horizontal Wells in Irregular Heterogeneous Reservoirs - Cheng Chang; Xuefeng Yang; Weiyang Xie; Dan Dai; Yizhao Chen; Xiaojing Ji; Yanzhong Liang; Bailu Teng (Energies)
The irregular outer boundaries of reservoirs and the associated heterogeneous high-permeability zones formed by complex geological environment pose significant challenges in reservoir characterization and performance prediction. These irregular geometries, which are commonly encountered in field applications but often oversimplified in conventional models, can substantially influence fluid flow dynamics and transient pressure behavior. To solve this critical issue, this paper presents a semi-analytical model for studying the transient pressure behavior of irregular heterogeneous reservoirs, focusing on the dynamic interactions between hydraulic fractures and the surrounding matrix. The model integrates Green’s function solutions for matrix flow with finite difference methods to simulate fluid flow within complex fracture networks, capturing the heterogeneity of the reservoir and the irregularity of its boundaries. Specifically, the reservoir is divided into locally homogeneous blocks, and the flow within each block is solved using bounded Green’s functions, while the fracture networks are discretized and solved using finite difference methods. This proposed model significantly reduces computational complexity compared to traditional numerical simulations, while maintaining high accuracy. Subsequently, we conducted comprehensive parameter sensitivity analyses. The calculational results show that a multi-fractured horizontal well in an irregular heterogeneous reservoir can observe the following flow regimes: bilinear flow, elliptical flow, and boundary-dominated flow. Longer fractures and higher conductivity enhance fracture flux by increasing the contact area and reducing flow resistance, respectively. However, these positive impacts are constrained by drainage area limitations as production progresses.